Greenhouse-Based Premium Horticulture Business Plan Design in Java: Business Model Canvas Approach - Ananti Yekti; Siwitri Munambar,; Fitria Naimatu Sadiyah; Mufidah Muis (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2026)
Embracing technologies and sustainable practices can lead to a competitive edge in horticulture. One of them is the use of greenhouses for premium horticultural cultivation. A business model is essential to highlight the competitiveness and sustainability of businesses. This study aimed to design a Business Model Canvas (BMC) of greenhouse-based premium horticulture business planning. The study starts from June–December 2024. It was conducted in six provinces on Java Island. There are thirty informants. The data used is primary and secondary data. Primary data was collected through questionnaires, in-depth interviews, observations, and focus group discussions. Secondary data is obtained from various sources of literature and company documentation. Data was analysed according to nine block of BMC. The BMC consists of nine blocks that explain the key elements of the business, which are: customer segments, value proportions, channels, customer relationships, revenue stream, key resources, key activities, key partnerships, and cost structure. The research results present the BMC elements that need to be noticed and carried out by greenhouse premium horticulture entrepreneurs in Java to make their business run well. It also can be a reference for investors who want to invest their capital in a premium horticulture business based on a greenhouse.